Low-frequency constant-permeability iron-based nanocrystalline magnetic core and preparation method and application thereof
Through force field and magnetic field heat treatment technology, the grain size and magnetic anisotropy of nanocrystalline magnetic core are controlled, and the problem of unstable magnetic permeability in the existing technology is solved, and the iron-based nanocrystalline magnetic core is realized in the low frequency range. Constant permeability, suitable for high frequency inductor applications.
Patent Information
- Application Number
- CN202411588565.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to obtain iron-based nanocrystalline magnetic cores with medium and low and constant magnetic permeability, and the existing heat treatment processes limit the application range of the magnetic core, especially in inductors in high-frequency, AC and DC superposition occasions. good.
By performing force-field heat treatment and magnetic field heat treatment on the iron-based amorphous magnetic core, the precipitation and orientation of nanocrystals are controlled, the movement of the magnetic domain wall is suppressed, and a constant magnetic permeability is achieved. Specific steps include heating to a preset temperature and pressurizing, then releasing pressure and performing magnetic field heat treatment, regulating grain size and magnetic anisotropy, and ensuring stability of magnetic permeability in the range of 1-100kHz.
The low-frequency constant magnetic permeability characteristics of iron-based nanocrystalline magnetic core at 1-100kHz frequency are realized, and the application stability and service life of the magnetic core in inductors in high-frequency, AC and DC superimposed occasions are improved.
Smart Images

Figure CN119252642A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic materials, and in particular relates to an iron-based nanocrystalline magnetic core with low-frequency constant magnetic permeability and a preparation method and application thereof. Background Art
[0002] As a new generation of "double green" energy-saving materials, iron-based amorphous / nanocrystalline soft magnetic alloys are widely used in new energy vehicles, photovoltaic energy storage, consumer electronics, mobile communications and other fields because of their excellent comprehensive soft magnetic properties, such as high saturation magnetic induction intensity, low coercive force, high magnetic permeability and low loss.
[0003] Iron-based amorphous / nanocrystalline soft magnetic alloys are usually made of amorphous strips by high-speed copper roller rapid cooling process from master alloys, and the amorphous strips are wound into amorphous magnetic cores. Amorphous magnetic cores generally need to undergo appropriate heat treatment processes to finely control the microstructure of the alloy, that is, a single magnetic α-Fe phase is precipitated on the amorphous matrix to transform into a two-phase coexistence structure of amorphous and nanocrystalline to form a nanocrystalline magnetic core. This special two-phase nanostructure is also the main reason why the nanocrystalline magnetic core exhibits excellent comprehensive soft magnetic properties. Therefore, the heat treatment process of the magnetic core plays a decisive role in obtaining high-performance iron-based nanocrystalline magnetic cores. However, the heat treatment processes in the prior art, such as conventional annealing in an atmosphere furnace (vacuum or N2), magnetic field annealing, etc., make the obtained nanocrystalline magnetic cores often show high magnetic permeability and greatly reduce the characteristics with the increase of frequency, which is not suitable for application scenarios with medium and low magnetic permeability and good frequency characteristics, limiting its application.
[0004] In order to obtain a medium-low and constant magnetic permeability, the industry usually performs tension annealing on amorphous strips before winding them into magnetic cores, aiming to reduce the magnetic permeability of nanocrystalline magnetic cores by inducing anisotropy under the action of external tension on the strips. During tension annealing of amorphous strips, on the one hand, if the external tension is too large, the amorphous strips are prone to brittle fracture during heat treatment, and if the external tension is too small, the effect of reducing magnetic permeability is limited; on the other hand, due to factors such as the heat treatment tension equipment fixture, strip width, and strip surface morphology, existing equipment can only perform tension annealing on narrow, flat-surfaced strips, and the wider the strip, the more uneven the tension; the more defects on the strip surface, the more likely the defects will become the fracture concentration points of tension annealing; in addition, due to the brittleness of crystallized strips, the strips after tension annealing are severely brittle, and there are problems of low efficiency, easy fracture, and low plasticity during winding into magnetic cores. Therefore, the existing technology of tension annealing amorphous strips to reduce the magnetic permeability of nanocrystalline magnetic cores has great limitations. It is difficult to obtain good nanocrystalline magnetic cores with medium-low and constant or relatively stable magnetic permeabilities, and they cannot be widely used in inductors in various high-frequency and AC and DC superposition situations.
[0005] Therefore, it is urgent to develop a preparation process for nanocrystalline magnetic cores, skipping the annealing process of the strip and directly processing the wound magnetic core, so as to reduce the magnetic permeability while making the nanocrystalline magnetic core have the characteristic of constant magnetic permeability. Summary of the invention
[0006] In view of the problem in the prior art that it is difficult to obtain nanocrystalline magnetic cores with medium-low and constant magnetic permeability, the present invention provides an iron-based nanocrystalline magnetic core with low frequency and constant magnetic permeability, and a preparation method and application thereof.
[0007] To achieve the above purpose, the following technical solutions are specifically included:
[0008] A method for preparing an iron-based nanocrystalline magnetic core comprises the following steps:
[0009] (1) heating the iron-based amorphous magnetic core to a preset temperature and pressurizing it to a preset pressure, and then cooling it to below 200° C. and releasing the pressure to obtain a pre-burned magnetic core; the preset pressure is greater than atmospheric pressure;
[0010] (2) The pre-burned magnetic core is subjected to a magnetic field heat treatment and, after cooling, an iron-based nanocrystalline magnetic core is obtained.
[0011] In the method of the present invention, the iron-based amorphous magnetic core is subjected to force field heat treatment and magnetic field heat treatment in sequence, so that the iron-based nanocrystalline magnetic core has the characteristic of constant magnetic permeability. Among them, under the force field heat treatment, on the one hand, the pressure promotes the precipitation of nanocrystal grains but inhibits the rapid growth of nanocrystal grains at the same time, and to a certain extent, the magnetic core is kept at a relatively low magnetic permeability and a relatively stable magnetic permeability by controlling the grain size; on the other hand, the existence of the pressure field can induce magnetic anisotropy inside the magnetic core, increase the domain wall energy, and the high domain wall energy prevents the movement of the domain wall, and to a certain extent, the magnetic permeability of the magnetic core is relatively low and the magnetic permeability is relatively stable by regulating the domain wall energy. The actual effect of magnetic field heat treatment is to induce grain orientation growth, that is, to promote the orientation of nanocrystal grains along the direction of magnetic field application, thereby inducing magnetic anisotropy and regulating the shape of hysteresis loop. The force field heat treatment and the magnetic field heat treatment cooperate with each other, and it is necessary to regulate the grain and domain wall energy by force field heat treatment, and then regulate the induced grain orientation growth by magnetic field heat treatment. Preferably, the preset temperature is 430-525℃.
[0012] The stability of the magnetic permeability of the magnetic core is related to the temperature of the force field heat treatment. When the preset temperature is within the range of 430-525°C, the temperature gradually increases, the effective magnetic permeability of the magnetic core gradually increases, and there is no obvious regularity in the rate of change of the magnetic permeability. However, in a temperature range slightly deviating from the above, the rate of change of the effective magnetic permeability of the magnetic core within the range of 1-100KHz is greater than 10%, and the stability of the magnetic permeability deteriorates significantly. It can be seen that at the above-mentioned force field heat treatment temperature, the iron-based nanocrystalline magnetic core of the present invention has a more stable effective magnetic permeability.
[0013] Preferably, in step (1), the preset pressure is 30-120 MPa.
[0014] The stability of the magnetic permeability of the magnetic core is related to the pressure of the force field heat treatment. When the preset pressure is in the range of 30-120MPa, the pressure gradually increases, and the magnetic permeability of the magnetic core and its rate of change decrease accordingly. Within the above pressure range, the magnetic core can have excellent magnetic permeability stability in the range of 1-100KHz. However, the greater the pressure, the higher the energy consumption and the pressure requirements for the equipment, the higher the cost, and too high pressure is not conducive to expanding production. Therefore, while being able to meet the actual performance requirements, it is reasonable to choose a relatively low pressure, which is more in line with the production conditions.
[0015] Preferably, in step (1), the heating rate when the iron-based amorphous magnetic core is heated to a preset temperature is 5-30° C. / min.
[0016] Preferably, in step (1), the cooling rate is 50-1000° C. / min; and the pressurization method includes at least one of inert gas pressure pressurization and mold extrusion pressurization.
[0017] The frequency used by the magnetic core is related to the stability of the magnetic permeability. The inventors of the present invention have found that during the force field heat treatment process, the heating rate is 5-30℃ / min and the cooling rate is 50-1000℃ / min. As the heating rate increases or the cooling rate increases, the effective magnetic permeability of the magnetic core and its rate of change decrease accordingly. In order to achieve the purpose of maintaining the stability of the magnetic permeability of the magnetic core, the heating rate and cooling rate can be increased to a certain extent, and the time of the force field heat treatment can be shortened to reduce the magnetic permeability of the magnetic core while maintaining a stable magnetic permeability.
[0018] Preferably, the inert gas includes at least one of argon and nitrogen.
[0019] Preferably, in step (2), the temperature of the magnetic field heat treatment is 350-430°C, the magnetic field intensity of the magnetic field heat treatment is 800-3000Gs, and the time of the magnetic field heat treatment is 10-300min, more preferably 60-120min.
[0020] The magnetic field intensity, temperature and time of magnetic field heat treatment have a certain influence on the magnetic permeability and stability of the magnetic core. After completing the force field heat treatment, increasing the magnetic field can reduce the magnetic permeability and its rate of change of the magnetic core, but with the increase of the magnetic field intensity, the degree of decrease of the magnetic permeability is not large. However, if the time of magnetic field heat treatment is too long or the temperature is too high, the grain size in the magnetic core will increase significantly, which will increase the magnetic permeability and its rate of change to a certain extent. From the production working conditions, the higher the temperature and the longer the time of magnetic field heat treatment, the increased production cycle and energy consumption. Therefore, the inventors of the present invention found that during the magnetic field heat treatment process, when the magnetic field intensity is 800-3000Gs, the temperature of magnetic field heat treatment is 350-430℃ and the time of magnetic field heat treatment is 10-300min, the magnetic core can maintain a high magnetic permeability stability at 1-100KHz.
[0021] Preferably, the iron-based amorphous core in step (1) is formed by winding an iron-based amorphous strip, and the magnetic field direction of the magnetic field heat treatment in step (2) is parallel to the width direction of the iron-based amorphous strip.
[0022] Preferably, in step (2), the cooling is natural cooling, and the cooling is from 100° C. to room temperature.
[0023] Preferably, in step (1), the iron-based amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%.
[0024] Further preferably, the iron-based amorphous magnetic core comprises Fe 73.5 Si 15.5 B7Cu1Nb3、Fe 73.5 Si 13.5 B9Cu1Nb3、Fe 63.5 Ni 10 Si 15.5 B7Cu1Nb3、Fe 63.5 Co5Ni5Si 15.5 B7Cu1Nb3、Fe 68.5 Co5Si 15.5 At least one of B7Cu1Nb3.
[0025] The method of the present invention is actually a heat treatment method, which is effective for a variety of iron-based alloys and is suitable for different types of amorphous magnetic cores.
[0026] Preferably, the magnetic permeability of the iron-based nanocrystalline magnetic core is constant at a frequency of 1-100 kHz.
[0027] Further preferably, the permeability change rate of the iron-based nanocrystalline magnetic core at a frequency of 1-100 kHz is ≤10%, more preferably ≤5%.
[0028] Generally, the magnetic permeability of an iron-based nanocrystalline magnetic core changes greatly at different frequencies, but in an inductor for high frequency, AC and DC superposition, the smaller the change in the magnetic permeability of the iron-based nanocrystalline magnetic core, the more stable the performance of the iron-based nanocrystalline magnetic core, and when used to prepare an inductor for high frequency, AC and DC superposition, the iron-based nanocrystalline magnetic core has a longer service life and a more stable use effect. The iron-based nanocrystalline magnetic core of the present invention can maintain high stability of magnetic permeability at 1-100kHz, which is more in line with the requirements for application in inductors for high frequency, AC and DC superposition.
[0029] Preferably, the magnetic permeability of the iron-based nanocrystalline magnetic core is 1300-35000.
[0030] Further preferably, the magnetic permeability of the iron-based nanocrystalline magnetic core is 1500-14999.
[0031] The present invention also provides an application of the iron-based nanocrystalline magnetic core in preparing an inductor for high frequency and AC and DC superposition occasions.
[0032] Compared with the prior art, the present invention has the following beneficial effects: the present invention can obtain an iron-based nanocrystalline magnetic core with low magnetic permeability by subjecting the iron-based amorphous magnetic core to force field heat treatment and magnetic field heat treatment in sequence, and the iron-based nanocrystalline magnetic core has the characteristic of constant magnetic permeability at a low frequency of 1-100kHz. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the X-ray diffraction (XRD) pattern of the homemade amorphous ribbon.
[0034] Figure 2 A comparison diagram of the magnetic domain structures between Example 1 (left) and Comparative Example 5 (right).
[0035] Figure 3 This is a physical picture of the iron-based nanocrystalline magnetic core of Example 1.
[0036] Figure 4 Graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of Examples 1 to 17.
[0037] Figure 5 This is a graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of comparative examples 1 to 5. DETAILED DESCRIPTION
[0038] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0039] The amorphous strips used in the following embodiments and comparative examples can be purchased from the market or prepared by conventional methods. The methods may include the following steps: (1) component proportioning; (2) master alloy smelting; and (3) obtaining the corresponding amorphous strips by strip spinning and strip winding.
[0040] Example 1
[0041] A method for preparing an iron-based nanocrystalline magnetic core comprises the following steps:
[0042] (1) The alloy Fe in atomic percentage 73.5 Si 15.5 B7Cu1Nb3 amorphous strip (self-made, its XRD results are shown in the attached Figure 1 ) is wound into an amorphous magnetic core, and then the amorphous magnetic core is placed in a furnace body, evacuated, filled with inert gas argon gas, so that there is a certain pressure in the system, and heated to a force field heat treatment temperature of 480°C at a heating rate of 10°C / min, and at the same time, argon gas is continuously filled to pressurize to a preset pressure of 80MPa; then, cooled at a cooling rate of 100°C / min, and the pressure is released after cooling to below 200°C until room temperature and normal pressure are obtained.
[0043] (2) The pre-burned magnetic core is placed in the magnetic field heat treatment furnace and heated to a magnetic field heat treatment temperature of 380°C at a heating rate of 10°C / min. At this time, a magnetic field parallel to the width direction of the magnetic core is applied, and the core is kept warm for 60 minutes under a magnetic field strength of 1500Gs. The core is cooled to room temperature along with the furnace to obtain an iron-based nanocrystalline magnetic core.
[0044] Examples 2-17 and Comparative Examples 1-5
[0045] The only difference between Examples 2-17 and Comparative Examples 1-5 and Example 1 is: in steps (1)-(2), the heating and cooling rates, force field heat treatment temperature, preset pressure, magnetic field intensity, magnetic field heat treatment temperature or holding time. See Table 1 for detailed differences.
[0046] Table 1
[0047]
[0048]
[0049] The performance of the iron-based nanocrystalline magnetic core prepared above was tested: the inductance L of the nanocrystalline magnetic core was tested using a Keysight Agilent 4294A precision impedance analyzer in an external magnetic field of 1A / m and a frequency range of 1kHz to 100kHz; the effective magnetic permeability μ e Obtained through the inductance L conversion formula:
[0050] μ e =(L×L e ) / (N 2 ×A e ),
[0051] Where, L is the core inductance, μ e is the effective magnetic permeability of the core, L e is the magnetic path length of the core, A e is the effective cross-sectional area of the core, and N is the number of coil turns (the test condition is 1 turn).
[0052] μ e Change rate % calculation method: μ e Change rate % = (μ e(1kHz) -μ e(100kHz) ) / μ e(1kHz) ×100%, μ e A rate of change less than 5% is considered constant permeability.
[0053] Table 2
[0054]
[0055] Combined with Table 2 and Appendix Figure 2 , 4 -5 analysis, from Examples 1-17 and Comparative Examples 1-5, it can be seen that in the method of the present invention, the temperature is first raised to a preset temperature and pressure under force field heat treatment, then rapidly quenched and cooled to below 200°C, and then subjected to magnetic field heat treatment. The present invention combines force field and magnetic field heat treatment, which can make the iron-based nanocrystalline magnetic core have a low, stable or constant effective permeability at 1-100KHz. In the above embodiments, the effective permeability is in the range of 1500-14999.
[0056] Under the force field heat treatment, on the one hand, the pressure promotes the precipitation of nano-crystal grains but at the same time inhibits the rapid growth of nano-crystal grains. To a certain extent, the magnetic core is kept at a relatively low magnetic permeability and a relatively stable magnetic permeability by controlling the grain size; on the other hand, the existence of the pressure field can induce magnetic anisotropy inside the magnetic core, increase the domain wall energy, and the high domain wall energy prevents the movement of the domain wall. To a certain extent, the magnetic permeability of the magnetic core is relatively low and the magnetic permeability is relatively stable by regulating the domain wall energy. The actual effect of the magnetic field heat treatment is to induce the oriented growth of grains, that is, to promote the orientation of nano-crystal grains along the direction of magnetic field application, thereby inducing magnetic anisotropy and regulating the shape of the hysteresis loop. The force field heat treatment and the magnetic field heat treatment are mutually coordinated. It is necessary to regulate the oriented growth of grains by the magnetic field heat treatment on the basis of regulating the grains and the magnetic domain wall energy by the force field heat treatment. The present invention regulates the grain size, state, magnetic anisotropy, the shape of the hysteresis loop, etc. by changing the heat treatment process to obtain a magnetic core with stable magnetic permeability at 1-100KHz. It can be seen from Examples 1-17 and Comparative Examples 3-5 that if the condition of applying a pressure greater than atmospheric pressure or a constant magnetic field is lacking, the magnetic core obtained cannot maintain the performance of low-frequency and low-constant magnetic permeability, and cannot achieve the performance requirement of the present invention of an effective magnetic permeability of 1500-14999 at a frequency of 1-100kHz.
[0057] The heating rate in Examples 2, 3, 1, and 4 gradually increases, and the effective magnetic permeability of the magnetic core and its rate of change decrease accordingly; the cooling rate in Examples 9, 1, and 10 gradually increases, and the effective magnetic permeability of the magnetic core and its rate of change decrease accordingly, and the cooling rate is significantly increased compared to the natural cooling temperature of 6-8°C / min. This is because the present invention is equipped with a quenching device during cooling, thereby achieving a higher cooling rate, so that the time required for the heating process and the cooling process is shorter. It can be found that the frequency used by the magnetic core is related to the stability of the magnetic permeability. At different frequencies, it is necessary to maintain a stable magnetic permeability of the magnetic core. The heating and cooling rates can be increased to a certain extent, and the time of force field heat treatment can be shortened to reduce the magnetic permeability of the magnetic core while maintaining a stable magnetic permeability.
[0058] In Comparative Example 1, Example 5, Example 1, Example 6 and Comparative Example 2, the temperature of the force field heat treatment gradually increases, and the effective magnetic permeability of the magnetic core gradually increases. There is no obvious regularity in the rate of change of the magnetic permeability. However, the temperature of the force field heat treatment of Examples 1, 5-6 is 430-525°C, and the effective magnetic permeability is 1500-14999 at a frequency of 1-100kHz, and the rate of change of the magnetic permeability is less than 5%; Comparative Examples 1 and 2 are 400°C and 560°C respectively, but the effective magnetic permeability of Comparative Example 1 (Comparative Example 1 is effectively compared with Example 7) is 1211-1381, and the rate of change of the magnetic permeability reaches 12.31%, and the effective magnetic permeability of Comparative Example 2 is 27116-32216, and the rate of change of the magnetic permeability is 15.83%. It can be seen that if the temperature of the force field heat treatment slightly deviates from the range of 430-525°C, the magnetic permeability of the magnetic core will change significantly, and the magnetic permeability and its stability need to be controlled, which can only be achieved under a specific force field heat treatment temperature. In addition, the pressure of the force field heat treatment also has a certain influence on the magnetic permeability and stability of the magnetic core. The pressure of the force field heat treatment of Examples 7, 1, and 8 gradually increases, and the magnetic permeability of the magnetic core and its rate of change decrease accordingly. The pressure of the force field heat treatment that can be selected by the present invention is 30-120MPa, and within this pressure range, from the effect of the temperature of the force field heat treatment on the magnetic permeability, the influence trends of temperature and pressure on the magnetic permeability are opposite. The force field heat treatment needs to simultaneously regulate the pressure and temperature in a relatively suitable range to better control the magnetic permeability of the magnetic core and achieve a higher stability of the magnetic permeability of the magnetic core at 1-100KHz.
[0059] The magnetic field intensity in the magnetic field heat treatment of Examples 11, 1, 12, and 13 gradually increases, the magnetic permeability of the magnetic core decreases slightly, and the magnetic permeability change rate of the magnetic core gradually decreases; the temperature in the magnetic field heat treatment of Examples 14, 1, and 15 gradually increases, and the magnetic permeability and its change first decrease and then increase. The time of the magnetic field heat treatment of Examples 16, 1, and 17 gradually increases, and the magnetic permeability and its change first decrease and then increase. It can be seen that the magnetic field intensity, temperature, and time of the magnetic field heat treatment have a certain effect on the magnetic permeability and stability of the magnetic core. Based on Examples 1, 11-17 and Comparative Example 4 (magnetic field intensity is 0), it can be seen that after completing the force field heat treatment, increasing the magnetic field can reduce the magnetic permeability and its change rate of the magnetic core, but with the increase of the magnetic field intensity, the degree of magnetic permeability decrease is not large, but if the time of the magnetic field heat treatment is too long or the temperature is too high, the grain size in the magnetic core will increase significantly, but the magnetic permeability and its change rate will increase to a certain extent, and from the production conditions, the higher the temperature and the longer the time of the magnetic field heat treatment, the increased production cycle and energy consumption.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an iron-based nanocrystalline magnetic core, characterized in that: The steps include: (1) heating the iron-based amorphous magnetic core to a preset temperature and pressurizing it to a preset pressure, and then releasing the pressure after cooling it to below 200° C. to obtain a pre-burned magnetic core; the preset pressure is greater than atmospheric pressure; (2) The pre-burned magnetic core is subjected to a magnetic field heat treatment and, after cooling, an iron-based nanocrystalline magnetic core is obtained.
2. The method for preparing the iron-based nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the preset temperature is 430-525° C., and the preset pressure is 30-120 MPa.
3. The method for preparing the iron-based nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the heating rate when the iron-based amorphous magnetic core is heated to a preset temperature is 5-30°C / min.
4. The method for preparing an iron-based nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the cooling rate is 50-1000°C / min; the pressurization method includes at least one of gas pressure pressurization and mold extrusion pressurization.
5. The method for preparing the iron-based nanocrystalline magnetic core according to claim 1, characterized in that: In step (2), the temperature of the magnetic field heat treatment is 350-430° C., the magnetic field intensity of the magnetic field heat treatment is 800-3000 Gs, and the time of the magnetic field heat treatment is 1-300 min.
6. The method for preparing the iron-based nanocrystalline magnetic core according to claim 1, characterized in that: The iron-based amorphous core in step (1) is formed by winding an iron-based amorphous strip. The magnetic field direction of the magnetic field heat treatment in step (2) is parallel to the width direction of the iron-based amorphous strip. The cooling is natural cooling.
7. The method for preparing an iron-based nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the iron-based amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%.
8. An iron-based nanocrystalline magnetic core obtained by the method for preparing an iron-based nanocrystalline magnetic core according to any one of claims 1 to 7.
9. The iron-based nanocrystalline magnetic core according to claim 8, characterized in that: The magnetic permeability of the iron-based nanocrystalline magnetic core is constant at a frequency of 1-100 kHz.
10. Use of the iron-based nanocrystalline magnetic core according to claim 8 or 9 in preparing inductor devices for high frequency and AC / DC superposition applications.
Citation Information
Cited By
Iron-based nanocrystalline magnetic core with low frequency and constant permeability, and preparation method therefor and use thereof
WO2026097699A1
